Votes for Sale: Essays on Clientelism in New Democracies - Louise Thorn Bøttkjær (Copenhagen Business School (CBS), 2019)
During electoral campaigns in new democracies, parties and candidates often employ clientelist strategies such as vote buying to mobilize electoral support. The academic consensus is that when voters are offered gifts or money in exchange for their votes, it has detrimental consequences for democratic and economic development. Therefore, it is imperative to explore to what extent, why, and how does clientelism occur in new democracies? A framing paper and four articles address this question using new survey data from South Africa and cross-country data from Africa and Latin America. The framing paper develops a conceptual framework of vote buying as a four-step process, validates why South Africa is a relevant setting for the study of clientelism and outlines the extensive data collection conducted for this dissertation. Using an unobtrusive measurement technique called the list experiment, the first article explores the level of vote buying during the 2016 municipal election campaign in South Africa. Furthermore, the first article provides a methodological contribution to the literature by conducting an experimental test of an augmented version of the list experiment against the classic list experiment and showing that the augmented procedure produces biased results. The second article examines why candidates employ vote buying as a strategy to mobilize electoral support when the ballot is nominally secret, which enables voters to renege on their vote bargain commitments and vote as they please. The third article explores why voters vote for corrupt candidates, which enhances our understanding of how clientelism can mitigate voters' willingness to punish corrupt politicians. The fourth article examines how the character of the electoral system affects the relationship between poverty and vote buying in Africa and Latin America. Overall, this dissertation increases our theoretical understanding and empirical knowledge of how widespread clientelism is in the developing world and why and under what conditions it flourishes. This dissertation contributes conceptually, methodologically, empirically, and substantially to the literature on clientelism and vote buying and has important implications for policy makers seeking to reduce the prevalence of clientelism in new democracies.
hdl:10398/9709
Keywords: 650